Mathematics anxiety phenomenon among students: a study on five selected programs in UiTM Melaka / Mohd Hafiz Mohammad Hamzah and Yusarima Muhamad - Mohammad Hamzah, Mohd Hafiz; Muhamad, Yusarima (Research Management Institute (RMI), 2012)
Students always think that Mathematics as a burden to their academic life where slowly they feel fear to Mathematics. This phenomenon is called the Mathematics anxiety. Mathematics anxiety is a learned emotional response to either following process: participating in a Mathematics class, listening to lecture, working through a Mathematics problem or discussing Mathematics. This research investigate the Mathematics anxiety phenomenon among students in Universiti Teknologi MARA Melaka inclusive only five selected course which are Diploma in Accountancy, Diploma in Business Study, Diploma in Public Administration, Diploma in Office Management and Pre-Diploma Commerce. There are many reasons why this Mathematics anxiety happens. Students who had a poor achievement or poor educational background in Mathematics subject only but not in other subject will generate a general dislike of Mathematics. Students who had a negative self-esteem experience had a large Mathematics anxiety level which might because of their social life where they like to compare themselves with their peers and always try to exceed them. The objectives of this research are to determine the Mathematics anxiety level among all of this five selected courses where we want to identify why this anxiety happen among students according to three main reasons which are educational background, student level of self-esteem and their social life. The primary data obtained from the questionnaire distributed to 30 selected students for each five selected courses. Mathematics Anxiety Rating Scale (MARS) will be used when designing the questionnaire. The data is then analyzed using the software SPSS to get the statistical result. A correlation analysis will also be used to determine the relationship between variables. Outcomes from this research will answer all the objectives of this research and will become a suggestions and ideas for a Mathematics lecturers and teachers to improve their teaching skills.